Potensi Mikoriza Vesikular Arbuskular (MVA) sebagai Biofertilizer pada Tanaman Jagung (Zea mays) - Kuntum Febriyantiningrum; Dwi Oktafitria; Nia Nurfitria; Nurul Jadid; Dewi Hidayati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2021)
Mining activities can cause environmental damage, and needs land rehabilitation efforts. One approach to land rehabilitation after mine is with repairing the ecosystem condition by improving the quality of the soil, with increase fertility and enriching soil nutrient content by providing a biofertilizer from microbe, such as mycorrhizal fungi.  This study aims to determine the potential use of vesicular arbuscular mycorrhizal fungus (MVA) as a biofertilizer by examining the effect of MVA on the growth of corn plant (Zea Mays). Applicated indigenus MVA was able to increase the absorption of phosphorus (P) nutrients in the soil by corn plant so it had an effect on increasing the height and diameter of the corn plant stalks. MVA has the potential as a basic material for making biofertilizer, so it can be used to improve soil quality and environment in ex-limestone mining areas.